MACRONUTRIENT CONTENT OF DRY LEAVES COMPOST BY VERMICOMPOSTING METHOD - Kasam Kasam; Fajri Mulya Iresha; Alhamdy Adytama; Abdul Mutolib; Rofiqul Umam; Felga Zulfia Rasdiana; Ali Rahmat (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2020)
Waste management is one of the criteria for the evaluation of Green campus and sustainable university. Organic waste takes place in concern because of the domination of waste in university, such as food waste and dry leaves waste. Mismanagement in dry leaves will promote the campus area to look dirty. One method to control the dry leaves waste is the vermicomposting process. The purpose of this research is to evaluate the macronutrient content of dry leaves compost after the vermicomposting process. The research was conducted in the Faculty of Civil engineering and Planning, Universitas Islam Indonesia, Yogyakarta. The vermicompost sample in this study refers to the quality standards according to SNI 19-7030-2004 regarding compost quality standards. The results of vermicompost content value are obtained on day 56 is Phosphor amounting to 0.194%, amounting to 0.129% Potassium, and C / N ratio of 7.73. From the data that has been obtained can be concluded that the results of vermicompost are less effective as organic compost compared to the standards.